2019
DOI: 10.1097/mao.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validity of Quantified Visually Enhanced Vestibulo-ocular Reflex Test to Detect Horizontal Semicircular Canal Hypofunction

Abstract: Objective: To investigate the clinical validity of the mathematical measured VVOR test results to detect horizontal semicircular canal hypofunction. Study Design: Prospective, nonrandomized, observational study. Setting: Tertiary referral center, hospital. Patients: Consecutive patients on first time visit to otoneurology unit. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Jorge Rey-Martinez tested the same patient over years and this patient consistently demonstrated enhanced eye velocity ( 41 ). The reliability has also been confirmed in repeated measures on other individual patients ( 42 , 43 ). The next question becomes: what could be the mechanism for such enhancement?…”
Section: Vor Gainmentioning
confidence: 63%
See 1 more Smart Citation
“…Jorge Rey-Martinez tested the same patient over years and this patient consistently demonstrated enhanced eye velocity ( 41 ). The reliability has also been confirmed in repeated measures on other individual patients ( 42 , 43 ). The next question becomes: what could be the mechanism for such enhancement?…”
Section: Vor Gainmentioning
confidence: 63%
“…In testing vHIT, some patients show enhanced eye velocity and so VOR gains >1.0 (40)(41)(42). In many cases a VOR gain >1.0 is probably due to incorrect calibration, but we asked the question whether it is possible that changes in fluid dynamics could result in systematically enhanced VOR gain, in particular could enhanced VOR gain be an indicator of endolymph hydrops.…”
Section: Enhanced Eye Velocitymentioning
confidence: 99%
“…20 To date, no such suspected lack of accuracy has been evident in the papers published concerning quantified VVOR testing performed with a vHIT. In a large cohort of patients with vestibular disorders, Rey-Martinez et al 7 [7][8][9] Nonetheless, as suggested by all these authors, the emerging quantified VVOR method should be improved to achieve better VOR quantification accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, previous studies have observed that VVOR gain values in healthy individuals were significantly lower at higher stimulation frequencies, in particular, above 2 Hz. 7,17 The reasons for this gain decay at higher frequencies are not clear, but it has been suggested that it could be a lack of accuracy of pupil tracking of the vHIT device during VVOR test data recording. Nevertheless, other mechanisms could also influence this gain decay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation